(untitled) (GnosisWisdom, 2025)
This study highlights the need to create the Autonomous University of the Native Communities of the Central Selva in Yurinaki, taking into account various sociodemographic and educational factors of the Perené district. This region is diverse, hosting native communities such as the Asháninka, Yanesha, Shipibo and migrants who speak different languages. Perené has the largest rural population in the province of Chanchamayo, and, despite the high rate of basic schooling, faces important challenges regarding access to higher education, which is only accessed by a small percentage of the population. The district also has high rates of illiteracy, especially among native communities, which underlines the need to implement inclusive educational policies. In addition, cultural and linguistic diversity demands an education that respects and promotes native traditions and languages, particularly Asháninka, which is why the importance of intercultural bilingual education (EIB) is proposed. This reflects the need to adapt education to diversity, strengthening educational infrastructure and offering more access opportunities to all sectors of the population.